Marketing e responsabilidade social corporativa: estudo de caso no setor de telecomunicações no Brasil - Menezes, Viviane Campos de (2012)
This research inspires itself in the recognition of an imminent need for a critical perspective on mainstream literature. In addition, it should be taken into consideration the importance of those new dimensions which are not object to marketing literature, especially for practitioners and stakeholders in emerging economies. The concept of OPM has become the central pillar of marketing in past years while the concept of social corporative responsibility has reinforced the instrumentalist e colonialist character of marketing. This kind of literature has been massively disseminated in an asymmetrical way, with no concern to the diversity of knowledge, culture e contexts. The dominant stream of micromarketing neglects the social, political and power aspects, while the minor stream of macromarketing incorporates fundamentals of economical politics which are more common in contexts in which the 'non-marketing' is dominant. This research illustrates, through the means of a case study, how the marketing discourse, despite its vital importance for wide and restrict legitimating purposes, has been day to day revealing its instrumentalist character, creating then, more and more gaps between theory and practice.